Quicken 2008 the missing manual - Biafore, Bonnie; Safari eBooks (Farnham : O'Reilly, 2008)
Demonstrates the personal finance program's most recent upgrade, discussing banking and bill-paying online, retirement planning, investment management, and tax preparation.
Includes index.
Electronic reproduction.
Keywords: Quicken (Computer file); Finance, Personal -- Data processing; Electronic books